NAFLD is a risk factor for the development of diabetic nephropathy in patients with T2DM - Usmani MH; Karan Saran Kapur; Ranjeet Singh Sisodiya (Asian Journal of Medical Sciences, 2023)
Background: Non-alcoholic fatty liver disease (NAFLD) and diabetes are two common health problems of global concern. Diabetic nephropathy (DN) is also a microvascular complication of diabetes. However, there is little knowledge about the relationship between NAFLD and DN. Aims and Objectives: The aim of this study was to know the association between NAFLD and DN in type 2 diabetes mellitus (T2DM) patients. Materials and Methods: A cross-sectional study was conducted on 136 patients of T2DM admitted to Sanjay Gandhi memorial Hospital, Rewa. Using abdominal ultrasonography, patients were grouped as patients, with NAFLD and patients without NAFLD. Then, patients were screened for DN (microalbuminuria) using the dipstick method. Liver and kidney function tests and complete blood count were performed along with FBS, PPBS, and HbA1c. Data were analyzed by appropriate statistical tests by Wizard 2® (Version 2.0.12 (259)) software. P<0.05 was considered significant. Results: In this study, 61 (44.85%) patients were found to have NAFLD, and 30 (49.81%) also had DN. Out of 75 (55.14%) non-NAFLD patients, 21 (28%) had DN. The data were statistically significant (OR: 2.4885, 95%, P=0.0120). The mean estimated glomerular filtration rate (eGFR) (mL/min/1.73 m2) among subjects with FIB4 score ≥2.67 was 77.33±9.54 and was less as compared to the mean eGFR among subjects with FIB4 score <2.67 (104.12±5.23) (student t-test, t (134)=2.247, P=0.026). Conclusion: NAFLD might be a risk factor for the development of DN in T2DM patients.